Análises de risco e perigo de movimento de massa, caracterização geotécnica e estabilidade de encostas na região metropolitana de Aracaju - Santos Neta, Belaniza Gaspar (2016)
One of the main reasons for the occurrence of natural disasters related to mass movements is the indiscriminate occupation of risk areas, driven by the growth of cities. Because of that, natural disaster risk management policies are given great emphasis, especially when it comes to flood and landslide phenomena. In the case of municipal risk management, a city of Aracaju, capital of the state of Sergipe, has not been highlighted with regard to the occurrence of gravitational movements on slopes. Despite a predominantly flat area of interest, they present several relief sites that are characterized by disordered occupation with poor buildings, where deforestation, cuts, landfills and absence of basic sanitation are some of the factors that contribute to a occurrence of landslides on the present slopes Areas. The aim of this work was to evaluate risk and danger levels in Aracaju's plumbing areas, as well as to perform a geotechnical characterization and stability analysis of specific slopes of the city, and thus collaborate with the public risk management companies of the City Identify areas subject to events involving mass movements from the study of the physical and environmental characteristics of the municipality. To that end, 16 slope sectors were selected, two methodologies were installed, a risk analysis and another landslide hazard analysis. A zoning of risk of mass movements was carried out using a qualitative methodology, where 4 risk-grade ranges were established, according to the characteristics observed in the chosen areas. The city of Aracaju presented 6% of sectors with low risk, 44% with medium risk, 31% with high risk and 19% with very high risk. The hazard analysis was performed with the aid of a semi-quantitative methodology using the Hierarchical Analysis Process (AHP). As well as a risk analysis, 4 hazard degrees were established to classify the analysis sectors. In this analysis, the sectors that presented low hazard corresponding to 37%, the medium hazard to 19%, the high hazard was attributed about 6% and 38% of the sectors were classified with very high hazard. Based on classifications, it becomes possible to delimit the areas subject to landslides, which allow a hierarchization of problems and technical support for a relationship with the affected communities. Among the 16 slope sectors studied, selected as the main slopes of sectors 1, 3, 11 and 14 for to perform the stability analysis by means of the OptumG2® software for the determination of slope safety factor, applying the strength reduction method (SRM). A geotechnical characterization of the soils of the four slopes was carried out in order to know how the properties of the materials and the resistance parameters of the soils. In the stability analysis, only the medium risk sector was evaluated as stable, while the others were evaluated as unstable and belong to sets with high and very high risk. Based on this, it was found that as slope stability analysis were consistent with the risk attributed to the sectors to which they belong.